Role of TGF-β/Smad Pathway in the Transcription of Pancreas-Specific Genes During Beta Cell Differentiation - Gao, Yuhua; Zhang, Ranxi; Dai, Shanshan; Zhang, Xue; Li, Xiangchen; Bai, Chunyu (Frontiers in Cell and Developmental Biology, 2019)
Autoimmune destruction of pancreatic beta cells causes absolute insulin deficiency and results in type 1 diabetes mellitus (T1DM). The substitution of healthy pancreatic beta cells for damaged cells would be the ideal treatment for T1DM; thus, the generation of pancreatic beta cells from adult stem cells represents an attractive avenue for research. In this study, a cocktail of factors was used to induce the differentiation of pancreatic beta cells from mesenchymal stem cells (MSCs). The differentiation program was divided into five stages, and the roles of the cocktail factors used during each stage were systematically elucidated. Activin A was found to phosphorylate Smad2 and Smad3 in stage III, thereby activating the TGF-β/Smad pathway. Meanwhile, the endocrine-specific transcription factor, Ngn3, and the pancreas-specific miRNAs, miR-375 and miR-26a, were dramatically elevated in stage III. We next demonstrated that Smad4, an important transcription factor in the TGF-β/Smad pathway, could bind to the promoter sequences of target genes and enhance their transcription to initiate the differentiation of beta cells. Use of SB-431542, an inhibitor of the TGF-β/Smad pathway, demonstrated in vivo and in vitro that this pathway plays a critical role in the production of pancreatic beta cells and in modulating insulin secretion. Thus, the TGF-β/Smad pathway is involved in the production of beta cells from adult stem cells by enhancing the transcription of Ngn3, miR-375, and miR-26a. These findings further underline the significant promise of cell transplant therapies for type 1 diabetes mellitus.